(untitled) (Philological Studies, 2019)
The article deals with the concept of the communicative speech category love and jealousy phenomenon. Sources of the concept are traced back to the works by M.Bakhtin and some modern researchers. The peculiarities of the jealousy phenomenon are analyzed using the material of the texts of epistolary genre: in particular A.S.Pushkin, F.M.Dostoevsky and V.V.Mayakovsky’s correspondence. The jealousy is represented in the sense structure of love letters in various forms: in the form of direct declarations of jealousy, in the form of references to others’ opinions as real and imaginary causes for jealousy, in the form of descriptions of dreams, etc. In addition, the fragments of letters illustrating answers to jealousy and excuses are also analyzed.